2017
DOI: 10.1016/j.dld.2017.07.010
|View full text |Cite
|
Sign up to set email alerts
|

Indicators of suboptimal tumor necrosis factor antagonist therapy in inflammatory bowel disease

Abstract: The majority of IBD patients showed suboptimal therapy with current anti-TNFs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
24
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(32 citation statements)
references
References 25 publications
6
24
1
Order By: Relevance
“…21 Despite some numerical differences in the incidences of suboptimal therapy with anti-TNF agents, the present study and previous studies are generally consistent in that more than half of UC patients experience suboptimal responses after initiating biologic therapies, highlighting the unmet need in the treatment of patients with moderate to severe UC. 17,18,21 The frequencies of indicators of suboptimal anti-TNF therapy were similar between previous Western studies and our study, except that fewer patients in our study experienced anti-TNF dose escalation. 17,18 The limited reimbursement for infliximab and golimumab dose escalation in contrast with adalimumab for UC in Korea might have been responsible for the low rates of dose escalation.…”
Section: Discussionsupporting
confidence: 87%
See 3 more Smart Citations
“…21 Despite some numerical differences in the incidences of suboptimal therapy with anti-TNF agents, the present study and previous studies are generally consistent in that more than half of UC patients experience suboptimal responses after initiating biologic therapies, highlighting the unmet need in the treatment of patients with moderate to severe UC. 17,18,21 The frequencies of indicators of suboptimal anti-TNF therapy were similar between previous Western studies and our study, except that fewer patients in our study experienced anti-TNF dose escalation. 17,18 The limited reimbursement for infliximab and golimumab dose escalation in contrast with adalimumab for UC in Korea might have been responsible for the low rates of dose escalation.…”
Section: Discussionsupporting
confidence: 87%
“…The risk of suboptimal response to anti-TNFs in our study appears to be largely similar to findings from the Western world. 17,18 A previous study using a U.S. com-mercial claims database from 2005 and 2013 showed that 72% and 91% of patients with UC experienced at least one suboptimal response after 12 and 36 months, respectively; these figures were numerically slightly higher than those observed in our study. 17 In contrast, a multinational study using UC patient data from Canada, France, Germany, Italy, Spain, and the United Kingdom reported that 64.1% of anti-TNF initiators experienced at least one suboptimal response within 2 years, which was lower than the frequencies from the U.S. study and those from our study.…”
Section: Discussioncontrasting
confidence: 76%
See 2 more Smart Citations
“…The concomitant use of steroids and immunosuppressants that we observed is high compared with reports in the literature. Medical records for patients with UC in Europe and Canada indicated initiation, or a dose increase, of a non-biologic treatment in combination with adalimumab or infliximab for 21% of patients within 2 years of starting biologic treatment 40 , and analysis of US claims data reported concomitant use of a non-biologic treatment within 1 year of initiation of a biologic in 23% of patients 39 .…”
Section: Discussionmentioning
confidence: 99%